2013 IEEE 24th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC) 2013
DOI: 10.1109/pimrc.2013.6666184
|View full text |Cite
|
Sign up to set email alerts
|

Doubly coded costas signals for grating lobes mitigation

Abstract: In this paper, a novel design scheme for radar signal is proposed. It is based on a modification of Costas codes design obtained by increasing the frequency separation of frequency hops beyond the orthogonality condition. This condition states that frequency separation between frequency hops should be at most equal to the inverse of bit duration of the code. Indeed, increasing frequency separation beyond this condition is sometimes needed in radar applications. However, this leads to the appearance of grating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In this section, other Costas codes are used to encode the initial Costas pulses. The doubly coded Costas signal consists in replacing rectangular pulses by another Costas signal [22]. Indeed, under some conditions upon secondary Costas parameters, we have shown that such a double Costas coding approach can be efficient in eliminating grating lobes.…”
Section: Proposed Designsmentioning
confidence: 99%
“…In this section, other Costas codes are used to encode the initial Costas pulses. The doubly coded Costas signal consists in replacing rectangular pulses by another Costas signal [22]. Indeed, under some conditions upon secondary Costas parameters, we have shown that such a double Costas coding approach can be efficient in eliminating grating lobes.…”
Section: Proposed Designsmentioning
confidence: 99%
“…The instantaneous frequency of up-chirp LFM is given by (1) Where, f0 is the radar center frequency, and µ= (2πB)/ is the LFM coefficient, B=bandwidth and  is pulse width. Similarly, the instantaneous frequency for down-chirp LFM is given by (2) Adding linear frequency modulation widens the bandwidth and because of this, the range resolution enhances by a factor equal to the time-bandwidth product [3]. Yet, the LFM has large side-lobes in matched filter output which is the major drawback for which amplitude weighting (windowing) or data tapering is required to reduce the side lobes.…”
Section: Introductionmentioning
confidence: 99%
“…The latter consists in introducing a second level coding in the sub‐pulses of the main Costas code (size M , pulse duration t p and frequency spacing Δ f ), using another Costas code (size L , pulse duration t s and frequency spacing Δ f s ). Parameters of main and sub‐pulse codes are chosen so that the overall AAF show reduced sidelobes especially in the presence of grating lobes due to the non‐fulfilment of the orthogonality condition (case normalΔf>false(1/tpfalse)) [21].…”
Section: Introductionmentioning
confidence: 99%